The Impact of National Lockdown as a Response to Covid-19 on Migrated Children: Evidence from Durban, South Africa - Tolla, Aden Dejene; Singh, Shanta B. (International Journal of Criminology and Sociology, 2021)
The Novel Coronavirus-2019 (COVID-19) has affected many countries from the beginning of 2020 as it began to spread across the globe. The response of most affected nations was to declare national lockdowns in varying severities. South Africa declared one of, if not the most, severe lockdown of all countries which was termed in the media as “hard lockdown”. This paper discusses the COVID-19 pandemic in South Africa and the effects of the national lockdown on children, more specifically children from migrated parents that have settled in South Africa. The research adopted a qualitative approach, coupled with a review of published literature from March-September 14, 2020, to develop an understanding of the effects of the national lockdown on children, from migrated families in Durban. Furthermore, qualitative data was collected through telephonic interviews with10 participants (parents). This paper established that although lockdowns have shown some evidence that they have flattened the curve of the rate of infected persons, it has not gone without any unintended consequences. One of them being its impact on the children of migrated parents. It postulates that lockdown measures may unintentionally cause harm to children both socio-economically, psychologically and in some cases abuse. The researcher recommended that radio and television broadcasting options for primary and secondary school programs.